2023
DOI: 10.1063/5.0132975
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of rotor unsteady forces and noise due to ingestion of grid-generated turbulence

Abstract: In many aeronautics and marine applications, the unsteady forces generated by propulsion rotors due to turbulence ingestion are a significant source of noise and create serious concerns. The understanding of rotor turbulence ingestion and the rotor noise generation mechanisms is vital to achieve an optimal design or apply noise control strategy. The current study is the first attempt to numerically investigate an underwater rotor ingesting grid-generated turbulence by large eddy simulation combined with the Ff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Rotor ingestion of grid turbulence was also studied recently by Wu et al. (2023), who conducted LES of the Sevik (1974) experiment involving the Sevik rotor behind a turbulence grid. Two grids of different spacings and bar diameters were considered, and the computed rotor unsteady-thrust spectra were shown to predict the experimental results better in terms of both the broadband content and the spectral hump at the BPF than the theoretical model.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Rotor ingestion of grid turbulence was also studied recently by Wu et al. (2023), who conducted LES of the Sevik (1974) experiment involving the Sevik rotor behind a turbulence grid. Two grids of different spacings and bar diameters were considered, and the computed rotor unsteady-thrust spectra were shown to predict the experimental results better in terms of both the broadband content and the spectral hump at the BPF than the theoretical model.…”
Section: Introductionmentioning
confidence: 96%
“…Several simulation techniques have been employed, including large-eddy simulation (LES) (e.g. Carolus, Schneider & Reese 2007;Wang, Wang & Wang 2015Wu et al 2023), hybrid methods combining Reynolds-averaged Navier-Stokes simulation with LES (e.g. Suzuki et al 2018Suzuki et al , 2019Arroyo et al 2019), and the lattice-Boltzmann method (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a lack of studies conducted which utilizes the grid-generated turbulence approach to examine the turbulence interaction with aerodynamic bodies immersed in the flow. More recently, Wu et al [43] reported one of the first successful attempts to investigated rotor-turbulence ingestion and noise generation from grid-generated turbulence using a solid grid setup.…”
Section: Introductionmentioning
confidence: 99%